ANALYSIS OF THE SITUATION OF ATTRACTING FOREIGN INVESTMENTS TO OUR COUNTRY'S ECONOMY - Butayev Javlonbek Innatillo; Nuriddinov Shakhzod (Modern American Journals, 2025)
This article provides an analysis of the international investment position of the Republic of Uzbekistan. The article is aimed at studying the country's place in the global economy and international investment flows. The analysis is carried out mainly by studying Uzbekistan's positions in terms of foreign direct investment (FDI) and other investment instruments. The international investment position (IIP) is related to the country's foreign debts, assets and other financial resources, which provides important information about the state's economic stability and integration with international markets. It also discusses the policies and strategies that should be implemented to strengthen the country's international investment position and create new opportunities. The article presents proposals on areas aimed at ensuring economic growth of Uzbekistan, increasing investment attractiveness and strengthening its international economic competitiveness.
Keywords: International investment position, foreign direct investment, currency risk, international financial flows, global economy, tax incentives.